Understanding the consequences of changes in the production frontiers for roots, tubers and bananas - Petsakos, Athanasios; Prager, Steven D.; Gonzalez Rodriguez, Carlos Eduardo; Gama, Arthur Chibwana; Sulser, Timothy B.; Gbegbelegbe, Sika; Kikulwe, Enoch Mutebi; Hareau, Guy (Elsevier, 2019)
The widely recognized role of roots, tubers and bananas (RT&Bs) in achieving food security and providing income opportunities in the world’s poorest regions will be challenged by socioeconomic and climate related drivers. These will affect demand and production patterns and increase pressure on farming systems. Foresight results presented in this paper show that the importance of RT&B crops for food security will likely increase by 2050 despite these challenges. Furthermore, investments targeted at yield growth appear to be more effective than marketing improvements in alleviating production constraints and in strengthening the role of RT&B crops in future food systems.